Genetics in public health - Shilpa Rai; Gunjan Kumar; Vinay Suresan; Alok Kumar Sethi; Vidya Bhushan (Wolters Kluwer Medknow Publications, 2021)
Genetics is considered a branch of science dealing with the study of heredity and variation in genes and genotype. A hybrid subspecialty of genetics and public health has come up in recent years. Public health genetics involves the application of genetics and molecular biotechnology in the improvement of community health and disease prevention. The Centers for Disease Control developed a framework comprising four essential public health functions and three critical issues associated with individual function. This review aims to highlight the integration of discoveries in genetic into public health. Scientific approach is required to study the impact of genetic discoveries on community health. Judicious assessment of the utility of genetic tests and development of standards and guidelines for reassuring superior genetic testing are critical steps in the process. Strong public health leadership to develop, implement, and evaluate disease intervention strategies is required for utilizing the advances in genetics for disease prevention. The critical issues that affect each function are partnerships and coordination; ethical, legal, and social issues; and education and training. An integrated and comprehensive scheme is required for the control of genetic diseases. Public health professionals shall help evolve, study, and propagate the scientific knowledge that would serve as a guide for public health action.